Hold Breath: Autonomic Neural Regulation of Innate Immunity to Defend Against SARS-CoV-2 Infection - Wang, Changle; Zhao, Yan; Qiao, Hongxiu; Gao, Zhiyun; Yang, Jing; Chuai, Xia (Frontiers in Microbiology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel member of the genus of betacoronavirus, which caused a pandemic of coronavirus disease 2019 (COVID-19) worldwide. The innate immune system plays a critical role in eliminating the virus, which induces inflammatory cytokine and chemokine secretion, produces different interferons, and activates the adaptive immune system. Interactions between the autonomic nervous system and innate immunity release neurotransmitters or neuropeptides to balance the excess secretion of inflammatory cytokines, control the inflammation, and restore the host homeostasis. However, more neuro-immune mechanisms to defend against viral infection should be elucidated. Here, we mainly review and provide our understanding and viewpoint on the interaction between respiratory viral proteins and host cell receptors, innate immune responses to respiratory viral infection, and the autonomic neural regulation of the innate immune system to control respiratory viruses caused by lungs and airways inflammation.